(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied the band structure, density of states and spatial localization of electron in twisted bilayer nanoribbons by means of tight binding calculation. In Chiral geometries, edge states are also related to the presence of zig-zag edge atoms, although they presented remarkable size effects. Physical properties of chiral graphene nanoribbons and general edges can have a stong dependence on chirality. We have analysed the properties of edge states in twisted bilayaer ribbons, explaining their energy dispersion and spatial localization. The different splittings were found in edge bands due to the inhomogeneous interplay coupling. For stacked zig-zag atoms the coupling was larger than corresponding edge states splitted apart, but edge states stemming from regions with stacking, where the interlayer coupling was smaller and gave rise to zero energy bands. We have also been found that in the edge regions where top and bottom zig-zag terminations were stacked, inter-ribbon tunneling between the dispersions less zero energy states created bonding and antibonding combination with energies away from the energy of the Dirac point. The obtained results were found in good agreement with previously obtained results.